Activity of Escherichia coli in producing electricity using a microbial fuel cell - العلي بدر; ناصر هاجر; صالح أحمد (Latakia University Journal -Biological Sciences Series, 2021)
Microbial fuel cells convert chemical energy produced by oxidation and reduction reactions carried out by microorganisms into electrical energy. In this research, electricity production by the isolated E.coli bacteria in the coastal marine waters of Lattakia city was studied and some factors that affect it were studied. The results of studying the effect of different concentrations of glucose (1-4) g/l in the value of the voltage produced in the microbial fuel cell during the incubation period, observed that the highest value of the electrical voltage was 791 mV when adding glucose at a concentration of 3 g/l. While the lowest value of voltage was recorded 250 mV at a 4 g/l glucose concentration. The results of the effect of the length of the salt bridge (4,8 and 12) cm in produced voltage value, observed that the highest voltage value was 624 mV by using a salt bridge of length 4 cm. Whereas, the lowest value of the produced voltage was recorded at 155 mV when the length of salt bridge was 12 cm. The results of this study showed that microbial fuel cells may be used to produce electricity by marine bacteria that oxidize organic matter and convert it into electrical energy, in addition to the possibility of using it in the treatment of sewage.